Aβ1–42 oligomer induces alteration of tight junction scaffold proteins via RAGE-mediated autophagy in bEnd.3 cells - Chan, Yuanjin; Chen, Wenjing; Wan, Wenbin; Chen, Yanjie; Li, Yaming; Zhang, Chunyan (Experimental cell research, 2018)
Compelling evidences have shown that amyloid-β (Aβ) peptide is one of the major pathogenic factors resulting in blood-brain barrier (BBB) disruption in Alzheimer's disease (AD). However, the mechanism underlying BBB breakdown remains elusive. In our present study, we employed murine brain capillary endothelial cells (bEnd.3) as an in vitro BBB model to investigate the role of autophagy in Aβ1–42 oligo induced BBB disruption. We first identified Aβ1–42 oligo cytotoxicity to bEnd.3 cells as observed in the reduced cell viability and downregulation of ZO-1, Occludin and Claudin-5. Based on the observation that both downregulated expression of p-mTOR/m-TOR and upregulated ratio of LC3-II/β-actin were induced by Aβ1–42 oligo, we then applied 3-MA, an inhibitor of autophagy, to test the role of autophagy in Aβ1–42 oligo induced Tight junction (TJ) proteins damage. Results have shown that 3-MA partially reversed Aβ1–42 oligo induced downregulation of ZO-1, Occludin and Claudin-5, which was further determined by LC3 siRNA. We also used rapamycin to activate autophagy and found that TJ proteins damage induced by Aβ1–42 was deteriorated even further. Given that the receptor of advanced glycation end-products (RAGE) is a pivotal receptor that mediates Aβ toxicity, RAGE siRNA was utilized to identify the involvement of RAGE in Aβ1–42 oligo induced autophagy. The results demonstrated a suppressed autophagy with increased p-mTOR/m-TOR and decreased LC3-II/β-actin as well as increased ZO-1, Occludin and Claudin-5 in transfected cells after Aβ1–42 oligo treatment, as compared to the non-transfected group. In summary, these results suggested that Aβ1–42 oligo induced TJ proteins disruption via a RAGE-dependent autophagy pathway.